2010
DOI: 10.1167/iovs.09-3372
|View full text |Cite
|
Sign up to set email alerts
|

Optical Functional Properties of the Boston Keratoprosthesis

Abstract: Purpose To evaluate the optical characteristics of the Boston Keratoprosthesis (KPro), identify glare sources, evaluate possible glare control, and examine the benefit of implanting when the fellow eye has normal vision. Methods Computed and optical-bench-measured point spread function (PSF) and glare sources were compared. A translucent plastic cornea was used to determine the impact of glare due to scatter in the cornea, and its control with a dark-iris tinted contact lens. The effect of glare in implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 13 publications
2
46
2
1
Order By: Relevance
“…11 Glare is a commonly reported symptom following OOKP surgery and has also been observed with other KPro surgery such as the Boston KPro. 6 The decline in visual acuity with increasing glare settings was similar to those reported with the Boston type 2 KPro.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…11 Glare is a commonly reported symptom following OOKP surgery and has also been observed with other KPro surgery such as the Boston KPro. 6 The decline in visual acuity with increasing glare settings was similar to those reported with the Boston type 2 KPro.…”
Section: Discussionsupporting
confidence: 76%
“…Sayegh et al observed that the change in visual acuity in patients implanted with a Boston type 2 KPro was decreased in an AfroCaribbean patient presumed to be because the darker skin pigment served as better protection from glare from the surrounding cornea. 6 We did not observe this effect in our two patients of Asian and Afro-Caribbean descent.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations